STRATEGIES OF SUCCESSFUL ENGLISH LANGUAGE LEARNERS AMONG THE UNIVERSITY STUDENTS IN IMPROVING SPEAKING SKILL - Sitompul, Hanna Elfrida; Asi, Natalina; Luardini, Maria Arina (Journal Compound: Improving the Quality of English Education, 2019)
This research investigates the strategies used by successful English language learners of Faculty of Teacher Training and Education of University of Palangka Raya in improving speaking skill. This research employed the modified Strategy Inventory for Language Learning (SILL) questionaires designed by Oxford (1990) and classroom observation to obtain data from 3 successful students of the fourth semester students studying at the English Department. The analysis of the data revealed that students used a high level (M=3.55) of language learning strategies to improve their English speaking skill. Among the learning strategies, metacognitive strategies (M=4.09) appeared to be the most frequently used strategies by the three students to improve their English speaking skill, followed correspondingly by compensation strategies (M=3.75), cognitive strategies (M=3.74), affective strategies (M=3.33), social strategies (M=3.06), and memory strategies (M=2.92). This finding showed that high motivation, level of language proficiency, and learning style have strong relationship with the use of students’ language learning strategy. The result also suggests that various of teaching strategies in the classrooms should be considered by the language teachers since the students have different preferences to learn. Highlighting the importance of learners’ metacognitive strategies is also recommeded without ignoring out the other strategies.